ETHICAL RELIGIOUS COMMUNICATION AS A FOUNDATION FOR BUILDING SOCIAL HARMONY IN THE ERA OF THE INDUSTRIAL REVOLUTION 4.0 - Ketut Yuniati (IAHN-TP Palangka Raya, 2019)
The religious ethics of communicating in this paper are communication ethics that are based on religious education, especially those originating from the education of Hinduism. Religious-ethics should be carried out in real-life every day given the dynamics and social changes that are very fast as part of the development of science and technology. Besides bringing a positive impact on improving the level of human life in the world, the development of science and technology cannot be denied giving negative sentiment to the degradation of human ethics and morality so as to distance people from their human nature, especially in terms of communication. In this era, communication is very vital because communication can lead to peace and also destruction. Hindu communication in a number of texts is very concerned about ethics, namely the rules of communication. The Hindu scriptures, the Vedas, mandate a great deal about ethics which must be upheld especially in relation to the practice of communication. The communication ethics aims to establish a common meaning between the communicant as the messenger, and the communicator as the recipient of the message. The similarity of meaning that is built up can avoid communication gaps. Communication ethics that is applied properly and correctly in the dimension of social life can build social harmony.